A Novel Germline Mutation in Exon 10 of the SMAD4 Gene in a Familial Juvenile Polyposis (Gut and Liver, 2013)
Familial juvenile polyposis (FJP) is a rare autosomal dominant hereditary disorder that is characterized by the development of multiple distinct juvenile polyps in the gastrointestinal tract and an increased risk of cancer. Recently, germline mutations, including mutations in the SMAD4, BMPR1A, PTEN and, possibly, ENG genes, have been found in patients with juvenile polyps. We herein report a family with juvenile polyposis syndrome (JPS) with a novel germline mutation in the SMAD4 gene. A 21-year-old man presented with rectal bleeding and was found to have multiple polyps in his stomach, small bowel, and colon. His mother had a history of gastrectomy for multiple gastric polyps with anemia and a history of colectomy for colon cancer. A review of the histology of the polyps revealed juvenile polyps in both patients. Subsequently, mutation screening in DNA samples from the patients revealed a germline mutation in the SMAD4 gene. The pair had a novel mutation in exon 10 (stop codon at tyrosine 413). To our knowledge, this mutation has not been previously described. Careful family history collection and genetic screening in JPS patients are needed to identify FJP, and regular surveillance is recommended.